PENERAPAN RADIO FREQUENCY IDENTIFICATION DALAM MEMBANGUN SISTEM KEAMANAN DAN MONITORING SMART LOCK DOOR BERBASIS WEBSITE - Syukuryansyah, Ridho; Setiyadi, Didik; Rofiah, Syahbaniar (Infotech: Journal of Technology Information, 2020)
Technology in this modernization era helps many workers and human needs. Various fields have been encroached upon by technology and one cannot be released again, one of which is security systems. The need for increased security is based on human needs for a sense of comfort with the assets they have in a safe condition and can be monitored from anytime and anywhere. This research aims to build a security system using RFID and Arduino which can be monitored through the website. An early warning system for unknown objects is also embedded therein using a magnetic switch sensor on the door, buzzer to create sound frequencies that can attract the attention of the surrounding environment and the Arduino camera module to capture images of objects. The results of this research RFID can facilitate access in and out of the door and increase security compared to conventional keys. Only registered / known objects can access the room through the door. In and out activities are monitored through a website that can be accessed anytime and anywhere.